The Handling of Covid-19 Pandemic in Indonesia from the Perspective of Nonmilitary Defense Strategy - Cato, Kartoli (Advances in Social Sciences Research Journal, 2020)
Pandemic coronavirus disease -2019 (COVID-19) resulted in various aspects of the life of Indonesian people, including aspects of defense and security. The defense state classifies threats into military threats, nonmilitary, and combined or hybrid threats. The epidemic of COVID-19 is a non - military threat with a public safety dimension against the national defense. The bureaucracy that has not been properly integrated, sectoral egos, and negative news about the pandemic have become obstacles in the handling of the COV ID-19 pandemic by the Government of Indonesia. This research aims to analyze the simple handling of the pandemic COVID-19 by the Indonesian Government from the perspective of nonmilitary defense principles. This becomes important to unravel and minimize the obstacles faced so that subsequent handling will be more effective and efficient. This paper uses descriptive analysis with a qualitative approach and a literature study. With the theory principles of defense strategy of nonmilitary, the author is looking at steps undertaken by Indonesia Government in handling the pandemic COVID-19. The principle of unity of command, coordination principle, the principle of anticipation, and the principle of transparency still need to be improved in a concrete way so that the handling of the pandemic COVID-19 is effective and efficient, could be reached. Building synergies and integrity policymakers consistently and continuously, inevitability to improve the defense state ability in the face of threats, military, nonmilitary and hybrid threats